Technical Scheme for Optimizing Urban and Rural Logistics Operations and Improving the Informatization of Rural Logistics - Zhong Zheng; Wanxian He; Ganglan Wei (Advances in transdisciplinary engineering, 2024)
In order to optimize the core problems encountered in the operation of urban and rural logistics and improve the informatization degree of rural logistics, the authors of this paper conduct research on the application of big data, cloud computing, and other technologies in urban and rural logistics and informatization. Based on the current problems, the authors adopt the hierarchical design, C/S architecture, and cloud API technology to improve the low level of informatization in urban and rural logistics, as well as optimize the dispersion and repetitive construction of logistics resources for logistics enterprises in urban and rural areas. Overall, a feasible sharing technology solution for urban-rural logistics informatization has been provided, providing a certain reference for optimizing urban-rural logistics operations and improving rural informatization issues.
Keywords: E-commerce and Technology Innovations